2019
DOI: 10.1016/j.bbmt.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Choosing a Reduced-Intensity Conditioning Regimen for Allogeneic Stem Cell Transplantation, Fludarabine/Busulfan versus Fludarabine Melphalan: A Systematic Review and Meta-Analysis

Abstract: A B S T R A C T Fludarabine with busulfan (FB) or melphalan (FM) are 2 more commonly used reduced-intensity conditioning (RIC) regimens for allogeneic stem cell transplantation (HCT).We present a systematic review and meta-analysis of studies comparing these 2 RIC regimens. We searched electronic databases from inception through November 1, 2017 for literature searches to identify relevant studies. A DerSimonian random effects model was used to measure efficacy outcomes; hazard ratios (HRs) and corresponding 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…The results of our experiment showed that Melphalan caused an increase in the values of pro-oxidant/antioxidant ratio, MDA levels, oxidative damage to plasma proteins and oxidative protein modification. This supports the results of previous studies, which demonstrated that cytotoxic effect of the drug is mediated through ROS-dependent cell death, in addition to alkylation of DNA and activation of the p53 pathway [36,37]. We observed only slight elevation of the other markers, which can be due to our experimental design: we assessed oxidative stress parameters on the 8th day after exposure to the alkylating agent, when the intensity of response has likely subsided.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our experiment showed that Melphalan caused an increase in the values of pro-oxidant/antioxidant ratio, MDA levels, oxidative damage to plasma proteins and oxidative protein modification. This supports the results of previous studies, which demonstrated that cytotoxic effect of the drug is mediated through ROS-dependent cell death, in addition to alkylation of DNA and activation of the p53 pathway [36,37]. We observed only slight elevation of the other markers, which can be due to our experimental design: we assessed oxidative stress parameters on the 8th day after exposure to the alkylating agent, when the intensity of response has likely subsided.…”
Section: Discussionsupporting
confidence: 91%
“…It also evaluates a protective potential of two forms of oral carbon adsorbent: primary solid beads (AC1) and orally disintegrating micronized form (secondary granules, AC2). Cytotoxic drugs, including alkylating agents, are among the most effective agents for treating advanced ovarian and breast cancer, haematological malignancies such as leukaemia, multiple myeloma, and others; these drugs are also used for reduced-intensity conditioning regimens in allogeneic stem cell transplantation [4,35,36]. Myelosuppression is a dose-limiting factor for chemotherapy schemes [20,21,37] and thus control of such side-effects improves chemotherapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…12 There have been several retrospective studies and a meta-analysis comparing the 2; however, these studies were limited by the inclusion of various age groups, disease-related factors, and graft-versus-host disease (GVHD) prophylaxis regimens. [14][15][16] In general, the results suggested a higher NRM but better disease control with FM RIC compared with FB and a variable effect on overall survival (OS). In the current study, we analyzed individual level data from a large cohort of AML transplantation patients from Center for International Blood and Marrow Transplant Research (CIBMTR) to compare the 2 RIC regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Our results add to a growing body of literature supporting the use of a melphalan‐based conditioning approach in myeloid malignancies, both in the submyeloablative and myeloablative contexts. There are numerous reports comparing melphalan‐ and busulfan‐based RIC regimens for AML/MDS in adult patients, which were recently reviewed in a meta‐analysis . AML/MDS patients (N = 1271) had superior OS with fludarabine/melphalan conditioning compared to submyeloablative busulfan/fludarabine conditioning (HR 0.83; 95% confidence interval 0.73‐0.95).…”
Section: Discussionmentioning
confidence: 99%
“…Regimens that carry reduced toxicity yet are still myeloablative may offer a balance between the risks of relapse and TRM. Melphalan‐based conditioning is widely used in RIC protocols, particularly in adult patients with decreased tolerance of MAC, with outcomes that compare favorably to busulfan‐based RIC regimens . Melphalan‐based RTC regimens have not been fully evaluated in children.…”
Section: Introductionmentioning
confidence: 99%